Presurgical Rehearsals for Patients Considering “Awake” Deep Brain Stimulation - Falconer, Ramsey A.; Rogers, Sean L.; Brewer, Cristie M.; Piscitani, Franco; Shenai, Mahesh B. (Frontiers in Surgery, 2016)
Simulated surgical environments are rapidly gaining adoption in training students, residents, and members of specailized surgical teams. However, minimal attention has been given to the use of simulated surgical environments to educate patients on surgical processes, particularly procedures that require the active participation of the patient. "Awake" neurosurgery provides a unique situation in which patients openly participate in their operation. We describe a case report, in which a 62 y.o. male was referred for "awake" deep brain stimulation (DBS) implantation, in relation to medically-refractory Parkinson's Disease. The patient had significant concerns regarding anxiety and clastrophobia, and toleration of the "awake" procedure. Consequently, we designed a simulated OR environment and process, to recreate the physical experience of the procedure, with minimal cost or risk. This experience was crucial in determining the care plan, as after this experience, the patient opted for an "asleep" alternative. Thus, in certain settings, presurgical rehearsals may have a dramatic impact in the overall course of care.